2015
DOI: 10.1111/phpp.12171
|View full text |Cite
|
Sign up to set email alerts
|

Factors that influence sunscreen application thickness and potential preservative exposure

Abstract: In this study, sunscreen users applied different amounts of sunscreen depending on the application method, affording different levels of sun protection. Typical use of the sunscreens is not likely to result in MI sensitization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…28 The quantity applied depends on the application method, which influences the thickness of sunscreen on the skin, as well as on the time spent on application. 29,30 As the most common reasons for rejecting sunscreen in our study were a too laborious usage and an inconvenient feeling on the skin, it might be helpful to elucidate that the use of sunscreen in the right way is inevitable for the protective effect. Therefore, a formulation leaving a convenient feeling on the skin and attractive designs (eg, small sunscreen sizes for the use on the go, dispenser, or sprays that enable a "no touch" application) can increase the popularity of sunscreen.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…28 The quantity applied depends on the application method, which influences the thickness of sunscreen on the skin, as well as on the time spent on application. 29,30 As the most common reasons for rejecting sunscreen in our study were a too laborious usage and an inconvenient feeling on the skin, it might be helpful to elucidate that the use of sunscreen in the right way is inevitable for the protective effect. Therefore, a formulation leaving a convenient feeling on the skin and attractive designs (eg, small sunscreen sizes for the use on the go, dispenser, or sprays that enable a "no touch" application) can increase the popularity of sunscreen.…”
Section: Discussionmentioning
confidence: 91%
“…Campaigns should point out how sunscreen is applied correctly, because an inappropriate application of sunscreen can lead to an insufficient UV protection . The quantity applied depends on the application method, which influences the thickness of sunscreen on the skin, as well as on the time spent on application . As the most common reasons for rejecting sunscreen in our study were a too laborious usage and an inconvenient feeling on the skin, it might be helpful to elucidate that the use of sunscreen in the right way is inevitable for the protective effect.…”
Section: Discussionmentioning
confidence: 99%
“…There were several behavioral studies on sunscreen use that aimed to identify the difference between theoretical UVPE (ie, labeled SPF) and actual UV protection and to find out ways to improve UV protection . Most of those studies showed that the amount of applied sunscreen in real‐life situations was significantly lower than the amount defined in the ISO24444.…”
Section: Discussionmentioning
confidence: 99%
“…There were several behavioral studies on sunscreen use that aimed to identify the difference between theoretical UVPE (ie, labeled SPF) and actual UV protection and to find out ways to improve UV protection. [8][9][10][11][12][13][29][30][31][32][33][34][35][36][37][38][39][40] Most of those studies showed that the amount of applied sunscreen in real-life situations was significantly lower than the amount defined in the ISO24444. The reported amounts varied from 0.1 to 1.6 mg/cm 2 , and this was probably caused by the formulations used, the situations, countries, examined areas, and weighing methods.…”
Section: Application For Behavioral Investigationsmentioning
confidence: 99%
“…The result of the quantity study may thus be affected by selection bias. Previous studies performed outside Denmark have also measured the quantity of sunscreen by weighing sunscreen bottles before and after application, most of the measurements being performed in laboratory environments (11)(12)(13). The trend is, however, that participants use smaller quantities of sunscreen in real-life situations.…”
Section: Discussionmentioning
confidence: 99%